Angiotensin AT4 ligands are potent, competitive inhibitors of insulin regulated aminopeptidase (IRAP) - Lew, Rebecca A.; Mustafa, Tomris; Ye, Siying; McDowall, Sharon G.; Chai, Siew Yeen; Albiston, Anthony L. (Journal of neurochemistry, 2003)
Angiotensin IV (Ang IV) exerts profound effects on memory and learning, a phenomenon ascribed to its binding to a specific AT4 receptor. However the AT4 receptor has recently been identified as the insulin‐regulated aminopeptidase (IRAP). In this study, we demonstrate that AT4 receptor ligands, including Ang IV, Nle1‐Ang IV, divalinal‐Ang IV, and the structurally unrelated LVV‐hemorphin‐7, are all potent inhibitors of IRAP catalytic activity, as assessed by cleavage of leu‐β‐naphthylamide by recombinant human IRAP. Both Ang IV and divalinal–Ang IV display competitive kinetics, indicating that AT4 ligands mediate their effects by binding to the catalytic site of IRAP. The AT4 ligands also displaced [125I]‐Nle1‐Ang IV or [125I]‐divalinal1‐Ang IV from IRAP‐HEK293T membranes with high affinity, which was up to 200‐fold greater than in the catalytic assay; this difference was not consistent among the peptides, and could not be ascribed to ligand degradation. Although some AT4 ligands were subject to minor cleavage by HEK293T membranes, none were substrates for IRAP. Of a range of peptides tested, only vasopressin, oxytocin, and met‐enkephalin were rapidly cleaved by IRAP. We propose that the physiological effects of AT4 ligands result, in part, from inhibition of IRAP cleavage of neuropeptides involved in memory processing.